Membrane electrode and application thereof

By using sulfur and/or nitrogen-modified supported platinum atomic cluster catalyst in the membrane electrode, the problem of low hydrogen precipitation reaction kinetics under alkaline conditions is solved, high current density and stability are achieved, and the amount of Pt is reduced, which promotes the commercialization process of water electrolysis hydrogen production technology.

CN119506940APending Publication Date: 2025-02-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311068398.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In the existing water electrolysis hydrogen production technology, the hydrogen precipitation reaction kinetics of the membrane electrode under alkaline conditions are low, resulting in the use of a large number of Pt-based catalysts for the cathode, which increases the cost and equipment volume.

Method used

The supported platinum atomic cluster catalyst modified with sulfur and/or nitrogen is used as the cathode catalyst for the membrane electrode. The dispersion and utilization of platinum are improved through the modification treatment and the amount of Pt is reduced.

Benefits of technology

The current density and stability of the membrane electrode are significantly improved, the amount of Pt is effectively reduced, the cost of the electrolytic cell is reduced, and the electrolytic efficiency and hydrogen production are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506940A_ABST
    Figure CN119506940A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrochemistry, and discloses a membrane electrode and application thereof.The membrane electrode comprises a diaphragm and a cathode diffusion layer, the side, adjacent to the diaphragm, of the cathode diffusion layer is coated with a cathode catalyst, and the cathode catalyst comprises a sulfur and / or nitrogen modified supported platinum cluster catalyst. The membrane electrode has excellent activity and stability when being applied to the hydrogen production process by electrolyzing water under the alkaline condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrochemical technology, and in particular to a membrane electrode and application thereof. Background Art

[0002] Hydrogen energy has the characteristics of high energy density, high calorific value, wide sources, clean and pollution-free. As countries pay more and more attention to global climate change and energy revolution, hydrogen energy, as a clean and efficient energy carrier, has become an important support for building a sustainable society. Hydrogen production by water electrolysis is currently a relatively mature and simple method to obtain hydrogen. Hydrogen production by water electrolysis is mainly divided into alkaline water electrolysis (ALK), proton exchange membrane (PEM) water electrolysis and anion exchange membrane (AEM) water electrolysis.

[0003] PEM water electrolysis technology is recognized as one of the most promising hydrogen production technologies due to its high electrolysis efficiency, safety and reliability, compact structure, and rapid response to renewable energy. However, due to the acidic high-voltage environment of PEM water electrolysis, only the precious metal Ir-based catalyst is relatively stable at its anode. As a byproduct of Pt, Ir has small reserves, and the amount of Ir used in PEM water electrolysis is large, resulting in high costs, which limits the commercialization of PEM water electrolysis. Alkaline water electrolysis is currently the most mature water electrolysis technology. It does not require the use of precious metals, making the equipment manufacturing cost very low, but its operating current density is very low, usually less than 0.5A / cm 2 , which results in the hydrogen production equipment being extremely large.

[0004] AEM can combine the advantages of PEM and alkaline water electrolysis, which can increase current density and reduce the use of precious metals. However, under alkaline conditions, the kinetics of hydrogen evolution reaction is 2-3 orders of magnitude lower than that under acidic conditions. At this time, hydrogen evolution reaction is very important. Whether it is ALK or AEM water electrolysis, to achieve a high current density (not less than 1A / cm 2 ), the cathode still needs to use Pt-based catalysts.

[0005] 40%-60% platinum carbon nanocrystalline catalyst is currently the most mature cathode catalyst for AEM water electrolysis. Due to the slow kinetics of hydrogen evolution and the difficulty of effectively utilizing the platinum inside the platinum nanocrystalline catalyst particles, a large amount of Pt-based catalyst is required to ensure the activity of the membrane electrode to ensure the current density and long-term operation stability of the electrolyzer. Therefore, while reducing the amount of precious metals used in the membrane electrode, improving the current density and stability of the membrane electrode is crucial to reducing the cost of the electrolyzer, improving its electrolysis efficiency and hydrogen production, and accelerating commercial applications. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a membrane electrode and its application. The membrane electrode is applied in the process of water electrolysis, especially in the process of hydrogen production by electrolysis of water under alkaline conditions, and has excellent activity and stability.

[0007] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a membrane electrode for hydrogen production by water electrolysis, wherein the membrane electrode comprises a diaphragm and a cathode diffusion layer, wherein a cathode catalyst is coated on one side of the cathode diffusion layer adjacent to the diaphragm, and the cathode catalyst comprises a supported platinum atomic cluster catalyst modified with sulfur and / or nitrogen.

[0008] Preferably, the platinum loading in the membrane electrode is not greater than 0.4 mg / cm 2 , more preferably not more than 0.1 mg / cm 2 .

[0009] Preferably, the cathode catalyst content in the membrane electrode is not more than 1.5 mg / cm 2 , more preferably not more than 1 mg / cm 2 .

[0010] Preferably, the sulfur and / or nitrogen modified supported platinum atomic cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8.

[0011] The second aspect of the present invention provides the use of the membrane electrode described in the first aspect in producing hydrogen by electrolysis of water under alkaline conditions.

[0012] Through the above technical scheme, compared with the prior art, the present invention has the following beneficial technical effects.

[0013] (1) The present invention significantly improves the dispersion of platinum and enhances mass transfer in the membrane electrode by using a supported platinum atomic cluster catalyst modified by sulfur and / or nitrogen, which is beneficial to increasing the current density of the electrolytic cell.

[0014] (2) The present invention improves the utilization rate of platinum and can effectively reduce the amount of Pt in the membrane electrode.

[0015] (3) In the present invention, there is a strong interaction between the carrier and Pt, which significantly improves the stability of the membrane electrode or electrolytic cell during long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the polarization curve of the membrane electrode in Example 1.

[0017] Figure 2 This is the constant current stability curve of the membrane electrode in Example 1.

[0018] Figure 3 This is the polarization curve of the membrane electrode of Example 2.

[0019] Figure 4 This is the constant current stability curve of Example 2.

[0020] Figure 5 This is the polarization curve of the membrane electrode of Example 3.

[0021] Figure 6 This is the polarization curve of the membrane electrode of comparative example 1.

[0022] Figure 7 This is the constant current stability curve of the membrane electrode of comparative example 1. DETAILED DESCRIPTION

[0023] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0024] The first aspect of the present invention provides a membrane electrode for producing hydrogen by water electrolysis, the membrane electrode comprising a diaphragm and a cathode diffusion layer, the cathode diffusion layer being coated with a cathode catalyst on one side adjacent to the diaphragm, the cathode catalyst comprising a supported platinum atomic cluster catalyst modified with sulfur and / or nitrogen.

[0025] In the present invention, the cathode diffusion layer being coated with a cathode catalyst on one side adjacent to the diaphragm means that in the membrane electrode, the cathode catalyst is coated on one side adjacent to the diaphragm of the cathode diffusion layer.

[0026] In the present invention, the platinum atom cluster catalyst refers to a catalyst in which the platinum metal particles do not have regular lattice fringes. Having lattice fringes means that the Pt particles exist in the form of nanocrystals.

[0027] In the present invention, the regular lattice fringes refer to the observation of platinum particles with lattices by TEM or STEM, and the lattice fringes are parallel, which is considered to have regular lattice fringes. Figure 1-7 As shown by the black parallel lines in the middle, it is considered to contain regular lattice fringes.

[0028] In the present invention, as long as the cathode catalyst layer includes a supported platinum atom cluster catalyst modified by sulfur and / or nitrogen, it is not required that all catalysts in the cathode catalyst layer are supported platinum atom cluster catalysts modified by sulfur and / or nitrogen. Preferably, all catalysts in the cathode catalyst layer are platinum-carbon catalysts modified by sulfur and / or nitrogen. More preferably, the platinum metal particles with regular lattice fringes in the platinum-carbon catalyst do not exceed 60%, preferably less than 50%, more preferably less than 40%, and further preferably less than 20% or less than 10%. Specifically, the lattice fringes can be confirmed by observation under TEM or STEM (preferably AC-TEM or AC-STEM).

[0029] The present invention also provides a membrane electrode for producing hydrogen by water electrolysis, characterized in that the membrane electrode comprises a diaphragm and a cathode diffusion layer, a cathode catalyst is coated on one side of the cathode diffusion layer adjacent to the diaphragm, and the cathode catalyst comprises a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst;

[0030] The nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, wherein the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV;

[0031] The sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, wherein the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in an XRD spectrum, or a ratio of a unit mass of platinum normalized peak intensity to a half-maximum full width of a Pt (111) characteristic peak is not greater than 0.8, and a ratio of a unit mass of platinum normalized peak intensity to a half-maximum full width of a Pt (200) characteristic peak is not greater than 0.5, and a Pt 4f 7 / 2 characteristic peak in an XPS spectrum is located above 71.6 eV.

[0032] According to a preferred embodiment of the present invention, the platinum loading in the membrane electrode is not greater than 0.4 mg / cm 2 , more preferably not more than 0.1 mg / cm 2 , more preferably 0.05-0.1 mg / cm 2. In the present invention, the platinum loading refers to the content of platinum in the cathode diffusion layer per unit area. Compared with the prior art, the platinum loading in the membrane electrode of the present invention is significantly lower, which reduces costs while ensuring the electrolysis effect. The platinum loading of the present invention is obtained by taking the average value after measuring 5 different positions of the membrane electrode with a handheld XRF analyzer and by ICP (after dissolving the Pt in the catalytic layer on the membrane electrode of a specific area with aqua regia, testing it with an ICP spectrometer).

[0033] According to a preferred embodiment of the present invention, the cathode catalyst loading in the membrane electrode is no more than 0.4 mg / cm 2 , more preferably not more than 0.1 mg / cm 2 , more preferably 0.05-0.1 mg / cm 2 .

[0034] According to a preferred embodiment of the present invention, the cathode catalyst content in the membrane electrode is not more than 1.5 mg / cm 2 , more preferably not more than 1 mg / cm 2 , more preferably 0.2-1 mg / cm 2 . In the present invention, the cathode catalyst content in the membrane electrode refers to the cathode catalyst content in the cathode diffusion layer per unit area. Compared with the prior art, the amount of cathode catalyst used in the membrane electrode of the present invention is significantly lower, which reduces costs while ensuring the electrolysis effect. In the membrane electrode of the present invention, the cathode catalyst content is obtained by weighing before and after coating.

[0035] According to a preferred embodiment of the present invention, the sulfur and / or nitrogen modified supported platinum atomic cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8.

[0036] Preferably, in the sulfur and / or nitrogen modified supported platinum atom cluster catalyst, the mass fraction of platinum is 1-70%.

[0037] In the present invention, the sulfur and / or nitrogen modified supported platinum atom cluster catalyst may be a platinum atom cluster catalyst modified with sulfur alone, a platinum atom cluster catalyst modified with nitrogen alone, or a platinum atom cluster catalyst modified with both sulfur and nitrogen.

[0038] Preferably, the sulfur- and / or nitrogen-modified supported platinum atom cluster catalyst comprises a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst.

[0039] Preferably, the nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, and the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.

[0040] Preferably, the sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, and the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.

[0041] Specifically, in the nitrogen-modified platinum-carbon catalyst, "there is no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8" means that the platinum in the nitrogen-modified platinum-carbon catalyst is at least mostly present in an amorphous phase, but it does not exclude the presence of a small amount of crystalline phase. As above, the presence of a small amount of crystalline phase does not affect the performance of the nitrogen-modified platinum-carbon catalyst in the membrane electrode.

[0042] Specifically, in the sulfur-modified platinum-carbon catalyst, "there is no Pt characteristic peak in the XRD spectrum, or the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5" means that the platinum in the platinum-carbon catalyst of the present invention is at least mostly present in an amorphous phase, but it does not exclude the presence of a small amount of crystalline phase. As above, the presence of a small amount of crystalline phase does not affect the performance of the sulfur-modified platinum-carbon catalyst in the membrane electrode.

[0043] In the present invention, the cathode catalyst includes a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst, which means that the cathode catalyst may include a nitrogen-modified platinum-carbon catalyst alone, may include a sulfur-modified platinum-carbon catalyst alone, or may include both a nitrogen-modified platinum-carbon catalyst and a sulfur-modified platinum-carbon catalyst. When both a nitrogen-modified platinum-carbon catalyst and a sulfur-modified platinum-carbon catalyst are included, there is no particular limitation on the content of each of the two, and any combination of the two is within the scope of protection of the present invention.

[0044] The present invention has a wide selection range for the content of platinum in the platinum-carbon catalyst. Considering the effect and cost comprehensively, preferably, in the nitrogen-modified platinum-carbon catalyst, the mass fraction of platinum is 1-20%, preferably 1-15%, more preferably 5-15%, and further preferably 7-12%, based on the total mass of the nitrogen-modified platinum-carbon catalyst. Preferably, in the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, more preferably 6-60%, and further preferably 7-40%, based on the total mass of the sulfur-modified platinum-carbon catalyst.

[0045] According to a preferred embodiment of the present invention, when the platinum content of the nitrogen-modified platinum-carbon catalyst is less than 6 mass %, the ratio of the normalized peak intensity per unit mass of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.5 and the ratio of the normalized peak intensity per unit mass of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4.

[0046] Preferably, the nitrogen element in the nitrogen-modified conductive carbon black exists in the form of pyrrolic nitrogen. Specifically, the XPS analysis of the nitrogen-modified platinum-carbon catalyst of the present invention only has characteristic peaks of pyrrolic nitrogen, but does not have characteristic peaks of other types of nitrogen.

[0047] According to the present invention, preferably, the nitrogen content in the nitrogen-modified conductive carbon black is 0.1-10% by mass, preferably 0.2-5% by mass.

[0048] According to the present invention, preferably, the nitrogen-modified conductive carbon black comprises conductive carbon black and nitrogen and oxygen elements compounded therein. Preferably, the nitrogen-modified conductive carbon black of the present invention does not contain other compound elements except nitrogen. Here, the "compound elements" in the present invention refer to nitrogen, phosphorus, boron, sulfur, fluorine, chlorine, bromine and iodine. More preferably, the nitrogen-modified conductive carbon black is composed of conductive carbon black and nitrogen and oxygen elements compounded therein.

[0049] According to the present invention, preferably, the nitrogen-modified platinum-carbon catalyst has a N 1s Except for the characteristic peak between 399-400.5eV, there is no other characteristic peak between 395-405eV.

[0050] The nitrogen-modified platinum-carbon catalyst described in the present invention is also described in detail in Chinese patent application 202210168801.3. The present invention hereby quotes all of 202210168801.3 to illustrate the present invention. The characterization method of the above parameters of the nitrogen-modified platinum-carbon catalyst is the same as 202210168801.3, which will not be repeated here.

[0051] According to a preferred embodiment of the present invention, in the sulfur-modified platinum-carbon catalyst, the total sulfur content in the sulfur-modified conductive carbon black is greater than or equal to the surface sulfur content, preferably the total sulfur content is more than 1.2 times the surface sulfur content, more preferably more than 1.5 times.

[0052] In the preferred sulfur-modified platinum-carbon catalyst of the present invention, by constructing a new conductive carbon black carrier structure modified by elemental sulfur, it is more conducive to loading platinum inside the carrier, so that the platinum-carbon catalyst has better electrocatalytic performance. More preferably, the total sulfur content in the sulfur-modified conductive carbon black is more than 1.7 times, more than 2 times, more than 3 times, etc., of the surface sulfur content, for example, 1.5-10 times. Wherein, the surface sulfur content represents the sulfur mass fraction measured by XPS analysis, and the total sulfur content represents the sulfur mass fraction measured by a sulfur-carbon analyzer.

[0053] Preferably, the total sulfur content in the sulfur-modified conductive carbon black is 0.1-8% by mass, more preferably 0.5-6% by mass.

[0054] Preferably, the surface sulfur content of the sulfur-modified conductive carbon black is 0.1-6% by mass, preferably 0.5-3% by mass.

[0055] The sulfur-modified platinum-carbon catalyst of the present invention may have a total sulfur content of, for example, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9 or 10 times the surface sulfur content. In addition, the total sulfur content may be 0.4 mass%, 0.5 mass%, 1 mass%, 1.5 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass%, 6 mass%, 7 mass% or 8 mass%, etc.; the surface sulfur content may be 0.1 mass%, 0.5 mass%, 1 mass%, 1.5 mass%, 2 mass%, 3 mass%, 4 mass%, 5 mass% or 6 mass%, etc.

[0056] Preferably, based on the total mass of the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, preferably 5-60%, more preferably 6-50%, and further preferably 7-40%.

[0057] Preferably, when the platinum content of the sulfur-modified platinum-carbon catalyst is less than 10 mass%, there is no Pt characteristic peak in the XRD spectrum of the sulfur-modified platinum-carbon catalyst, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.6 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4.

[0058] Preferably, the sulfur-modified platinum-carbon catalyst has a Pt 4f 7 / 2 characteristic peak located above 71.7 eV, preferably above 71.9 eV in the XPS spectrum. The above XPS spectrum refers to the XPS spectrum corrected with the C1s peak located at 284.3 eV. Under normal circumstances, such as when platinum is loaded on a carbon carrier without composite elements, the Pt 4f 7 / 2 characteristic peak is located near 71.4 eV, which indicates that the sulfur-modified platinum-carbon catalyst of the present invention has a Pt 4f 7 / 2 characteristic peak shifted to high electron volts by more than 0.3 eV, preferably more than 0.5 eV in the XPS spectrum.

[0059] Preferably, the platinum-carbon catalyst of the present invention does not contain any other active metal elements except platinum.

[0060] According to the present invention, preferably, the sulfur-modified conductive carbon black comprises conductive carbon black and sulfur and oxygen elements compounded therein. Furthermore, the sulfur-modified conductive carbon black of the present invention preferably does not contain other compound elements except sulfur. More preferably, the sulfur-modified conductive carbon black consists of conductive carbon black and sulfur and oxygen elements compounded therein.

[0061] The sulfur-modified platinum-carbon catalyst described in the present invention is also described in detail in Chinese patent applications 202211515045.3 and 202211515010.X. The present invention hereby fully references 202211515045.3 and 202211515010.X to illustrate the present invention. The characterization method of the above parameters of the sulfur-modified platinum-carbon catalyst is the same as 202211515045.3 and 202211515010.X, which will not be repeated here.

[0062] As the conductive carbon black that can be used in the present invention, one or more of ordinary conductive carbon black (Conductive Blacks), super conductive carbon black (Super Conductive Blacks) or extra conductive carbon black (Extra Conductive Blacks) can be used, such as Ketjen black, Cabot conductive carbon black (Cabot, Black pearls, etc.), Oliron conductive carbon black (HIBLACK, PRINTEX, etc.), etc., specifically, it can be one or more of EC-300J, EC-600JD, ECP600JD, VXC72, VXC72R, Black pearls 2000, PRINTEX XE2-B, PRINTEX L6 and HIBLAXK 40B2.

[0063] The present invention has no limitation on the preparation method and source of the conductive carbon black, which may be acetylene black, furnace black, or the like.

[0064] Preferably, in the XPS analysis of the conductive carbon black, the oxygen content is greater than 4% by mass, for example, 5-12% by mass.

[0065] Preferably, the resistivity of the conductive carbon black is less than 10Ω·m, preferably less than 5Ω·m, more preferably less than 3Ω·m, and further preferably 0.01-1Ω·m.

[0066] Preferably, the specific surface area of ​​the conductive carbon black is 200-2000m 2 / g, preferably 220-1500m 2 / g. The specific surface area can be measured by the BET method.

[0067] The preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen in the present invention has a wide range of selection, and as long as the above parameter limitations are met, it is more conducive to improving the performance of the membrane electrode of the present invention. Preferably, the preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen comprises the following steps:

[0068] (1) nitrogen-modifying and / or sulfur-modifying conductive carbon black to obtain nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black;

[0069] (2) removing the solvent from the uniform mixed solution containing nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black, a platinum source and a solvent to obtain a precursor material;

[0070] (3) heat treating the precursor material obtained in step (2) at 80-200° C. for 1-4 h in a reducing atmosphere to obtain a platinum atomic cluster catalyst;

[0071] Wherein, in step (1), the nitrogen modification of the conductive carbon black comprises: after the conductive carbon black is contacted with a nitrogen source in an aqueous solution, the water is removed, and the obtained product is subjected to high temperature treatment under an inert atmosphere to obtain nitrogen-modified conductive carbon black; preferably, the conditions of the high temperature treatment include: a temperature of 1000-1500° C. and a constant temperature time of 0.5-10 h;

[0072] Wherein, in step (1), sulfur-modifying the conductive carbon black comprises: impregnating the conductive carbon black with a solution containing sulfur at 10-80° C. for 1-5 hours, and drying the impregnated product to obtain sulfur-modified conductive carbon black.

[0073] Preferably, the nitrogen source is ammonia water and / or urea, and the mass ratio of the conductive carbon black to the nitrogen source calculated by the mass of the nitrogen element is 30:1-1:2.

[0074] Preferably, the solvent in the sulfur-containing solution is one or more of CCl4, CS2, cyclohexane, and n-hexane.

[0075] More preferably, the concentration of sulfur in the sulfur-containing solution is 0.0004-0.02 g / mL.

[0076] Preferably, the amount of sulfur used is 0.005-0.06 g relative to 1 g of the conductive carbon black.

[0077] According to the present invention, preferably, in step (2), the platinum source is one or more of chloroplatinic acid, chloroplatinate, tetraamineplatinum acetate and platinum acetylacetonate.

[0078] In step (2), the solvent is preferably one or more of water, an alcohol solvent or a ketone solvent.

[0079] Preferably, the amount of the platinum source used is 0.01-2.4 g in terms of platinum element relative to 1 g of the nitrogen-modified conductive carbon black and / or the sulfur-modified conductive carbon black.

[0080] According to a preferred embodiment of the present invention, in step (3), the reducing atmosphere comprises hydrogen, preferably a mixed atmosphere of hydrogen and an inert gas, more preferably a mixed atmosphere of hydrogen and nitrogen; preferably, hydrogen accounts for 5-30 volume % of the total gas.

[0081] The detailed preparation of the nitrogen-modified platinum-carbon catalyst is the same as described in 202210168801.3, all of which are cited in the present invention and will not be repeated here.

[0082] The detailed preparation of the sulfur-modified platinum-carbon catalyst is the same as described in 202211515045.3 or 202211515010.X, all of which are cited in the present invention and will not be repeated here.

[0083] In the present invention, "carbon black" and "carbon black" are interchangeable technical terms.

[0084] The "inert gas" in the present invention refers to a gas that does not cause any appreciable effect on the properties of the sulfur / nitrogen modified conductive carbon black in the preparation method of the present invention.

[0085] The present invention has no particular limitation on the coating method of the cathode catalyst on the side of the cathode diffusion layer adjacent to the diaphragm, and various coating methods commonly used in the art may be used, preferably spraying, scraping or screen printing.

[0086] The present invention has no particular limitation on the parameters of the coating process, as long as a membrane electrode having the above parameters can be obtained by coating. Those skilled in the art can make an adaptive selection based on the above disclosure.

[0087] According to the present invention, preferably, the cathode diffusion layer adjacent to the diaphragm is coated with a cathode catalyst and may also contain other additives. There is no particular limitation on the type of the additives, which may be various additives conventionally used in the art, such as polytetrafluoroethylene or ionomers.

[0088] Preferably, the side of the cathode diffusion layer adjacent to the diaphragm is also coated with an ionomer, and preferably the mass ratio of the cathode catalyst to the ionomer is 70-92:8-30.

[0089] The present invention has a wide range of choices for the type of ionomer, for example, the ionomer can be provided by removing the solvent from a PBPA (poly(biphenylene alkylene) type ionomer) solution.

[0090] According to a preferred embodiment of the present invention, the coating method of the cathode catalyst and the ionomer includes: coating the slurry to be coated on one side of the cathode diffusion layer and drying; the slurry to be coated includes a supported platinum atom cluster catalyst modified by sulfur and / or nitrogen, an ionomer solution and a solvent. The drying described in the present invention is used to remove the solvent in the slurry to be coated, and its specific operation is not particularly limited. It can be carried out during the coating process, that is, heating while coating (such as drying), or the drying can be carried out after the coating is completed. Those skilled in the art can make appropriate choices based on actual production.

[0091] In the present invention, the ionomer solution (e.g., PBPA solution) is used to conduct hydroxide ions and bind catalysts. There is no particular limitation on the source of the ionomer solution, which can be obtained commercially. The amount of the ionomer solution (e.g., PBPA solution) can be selected in a wide range. Preferably, the mass amount of the ionomer solution (e.g., PBPA solution) is 0.9-4.5 times that of the cathode catalyst.

[0092] Preferably, the solvent includes water and a dispersing solvent, and the dispersing solvent is preferably selected from C1-C4 alcohols. Further preferably, the dispersing solvent is isopropanol and / or ethanol. The volume ratio of water to the dispersing solvent is 1:1-4.

[0093] The present invention has a wide range of selection for the amount of the solvent, based on the purpose of achieving uniform coating of the slurry on the cathode diffusion layer. Preferably, the amount of the solvent is such that the content of the catalyst in each milliliter of the slurry is 5-150 mg.

[0094] The present invention has no particular limitation on the specific selection of the cathode diffusion layer, and it can be any diffusion layer that can be used in the membrane electrode for hydrogen production by water electrolysis. The diffusion layer is used to support the catalyst, stabilize the electrode structure, and provide a gas channel, an electron channel, and a water supply channel for the electrode reaction. Preferably, the cathode diffusion layer is selected from a porous carbon material, preferably at least one of carbon paper, carbon cloth, and carbon felt.

[0095] The present invention has no particular limitation on the specific selection of the diaphragm, and it can be various diaphragms that can be used in water electrolysis hydrogen production membrane electrodes, especially various diaphragms that can be used in alkaline water electrolysis hydrogen production membrane electrodes. Preferably, the diaphragm is selected from at least one of anion exchange membrane, PPS (polyphenylene sulfide) diaphragm and asbestos cloth.

[0096] According to the present invention, the anion exchange membrane refers to a membrane capable of conducting anions, and there is no particular limitation on its type and source, and it can be homemade or commercially available. For example, the source of the anion exchange membrane includes, but is not limited to: Xiamen Jiamo KMem AE01, Huizhou Yiwei Alkymer W-25, American Dioxide Materials Company Sustanion X37-50, American Versogen PiperION, German Fumasep FAAM, Xion AEM-Durion, Xion AEM-Pention, Xion AEM-Dappion and other series of anion exchange membranes.

[0097] It should be noted that the PPS diaphragm described in the present invention refers to its broad meaning, and any modified PPS diaphragm is also within the protection scope of the present invention.

[0098] According to a specific embodiment of the present invention, the membrane electrode further comprises an anode diffusion layer, and the diaphragm is disposed between the anode diffusion layer and the cathode diffusion layer. It should be noted that the present invention has no particular limitation on the specific structure of the membrane electrode, and it can be assembled according to conventional means in the art. As long as the diaphragm is disposed between the anode diffusion layer and the cathode diffusion layer, the diaphragm can be in contact with or not in contact with the anode diffusion layer and the cathode diffusion layer, respectively.

[0099] The present invention has a wide range of selection for the type of the anode diffusion layer. Preferably, the anode diffusion layer is selected from at least one of titanium foam, titanium felt, titanium mesh, nickel foam, nickel mesh and nickel felt.

[0100] According to a preferred embodiment of the present invention, the anode diffusion layer is coated with an anode catalyst on one side adjacent to the diaphragm. The anode catalyst can be any catalyst conventionally used in the art, including but not limited to iridium oxide, nickel oxide, iron oxide, cobalt oxide, nickel ferrite, nickel-iron double hydroxide, nickel sulfide, nickel-iron-cobalt oxide and nickel-iron-cobalt hydroxide.

[0101] The specific coating method of the anode catalyst may refer to that of the cathode catalyst, and the present invention has no particular limitation on this.

[0102] According to a particularly preferred embodiment of the present invention, the method for preparing the membrane electrode comprises:

[0103] (1) providing a cathode slurry to be coated containing a supported platinum atom cluster catalyst modified with sulfur and / or nitrogen, an ionomer and a solvent; providing an anode slurry to be coated containing an anode catalyst, an ionomer and a solvent;

[0104] (2) applying the cathode slurry to be coated on the cathode diffusion layer, applying the anode slurry to be coated on the anode diffusion layer, and drying;

[0105] (3) A cathode diffusion layer coated with a cathode catalyst, a diaphragm, and an anode diffusion layer coated with an anode catalyst are stacked in sequence (wherein the sides of the cathode diffusion layer and the anode diffusion layer coated with catalysts are adjacent to the diaphragm) to obtain a membrane electrode.

[0106] The second aspect of the present invention provides the use of the membrane electrode in the production of hydrogen by electrolysis of water under alkaline conditions, preferably in the production of hydrogen by electrolysis of water using alkaline electrolysis of water (ALK) or anion exchange membrane (AEM), preferably in the production of hydrogen by electrolysis of water using AEM. Specifically, the membrane electrode provided by the present invention can be applied to an AEM electrolyzer, and there is no particular limitation on the arrangement of the membrane electrode in the AEM electrolyzer and the specific process and conditions for hydrogen production, and those skilled in the art can make an adaptive selection according to conventional means.

[0107] More preferably, in the application, the current density is not less than 0.8 A / cm 2 , for example 0.8-6A / cm 2 , more preferably not less than 1A / cm 2 , and the current density is preferably 1-6A / cm 2 .

[0108] Preferably, the alkaline condition has a pH of no less than 8.

[0109] According to the application of the present invention, the alkaline condition refers to maintaining the membrane interface in an alkaline condition during the electrolysis process, for example, water can be introduced as the electrolyte, and during the electrolysis process, the anion exchange membrane interface is maintained in an alkaline condition, and an alkali solution can also be introduced as the electrolyte. The present invention has no particular limitation on this.

[0110] The present invention will be described in detail below through examples. The PBPA solution was purchased from Xiamen Jiamo Company with the brand name KMem Al01. The anion exchange membrane was purchased from Xiamen Jiamo Company with the brand name KMem AM01. The cathode diffusion layer was carbon paper purchased from Wuhu Owl Material Technology Co., Ltd. with the brand name TPG-H-060. The anode diffusion layer was nickel foam purchased from Wuhu Owl Material Technology Co., Ltd. with a thickness of 1 mm.

[0111] Example 1

[0112] Preparation of 40wt% Pt / C catalyst: 0.55g sulfur was dissolved in 70ml cyclohexane to form a homogeneous solution, 9.45g Ketjenblack ECP600JD was dispersed therein, stirred evenly, immersed for 5h, and vacuum dried at 50°C to obtain sulfur-containing conductive carbon black as a sulfur-containing carbon carrier; 0.40g chloroplatinic acid was dissolved in 20mL water: ethanol volume ratio of 10:1, 0.6g of the above sulfur-containing carbon carrier was dispersed in the chloroplatinic acid solution, wherein the stirring and dispersion was uniform, and after standing for 24h, it was placed in a vacuum drying oven for drying; the dried precursor was placed in a tube furnace, raised to 140°C at a rate of 5°C / min, reduced for 2h in an atmosphere of N2:H2=5:1, and cooled down in an N2 atmosphere to obtain a platinum-carbon catalyst. The composition and structural parameter characterization results of the platinum-carbon catalyst refer to Examples 1-4 of 202211515010.X.

[0113] (1) Prepare the slurry to be coated

[0114] Cathode slurry to be coated: weigh 16 mg of 40 wt% Pt / C catalyst, add 322 μL of water, disperse evenly, add 1.28 mL of isopropanol and 53.35 mg of 10 wt% PBPA ionomer solution, mix evenly and set aside.

[0115] Anode slurry to be coated: weigh 32 mg of homemade NiFe double metal hydroxide catalyst (the molar ratio of Ni to Fe is 5:1), add 637 μL of water, disperse evenly, add 2.56 mL of isopropanol and 36.1 mg of 10 wt% PBPA ionomer solution, mix well and set aside.

[0116] (2) Membrane electrode preparation

[0117] The spraying method is used to coat the effective area of ​​16cm 2 The cathode slurry to be coated and the anode slurry to be coated are coated on the carbon paper and the nickel foam, so that the loading amount of the cathode catalyst in the membrane electrode is 1 mg / cm 2 The loading of the anode nickel-iron based catalyst is 2 mg / cm 2 Finally, the catalyst-loaded membrane electrode was cut into 2 cm*2 cm, and then the diffusion layer coated with the anode catalyst, the diaphragm, and the diffusion layer coated with the cathode catalyst were stacked in sequence (the side of the cathode diffusion layer and the anode diffusion layer coated with the catalyst was adjacent to the diaphragm), and the effective area was 4 cm 2 The membrane electrode was installed in the electrolytic cell for testing.

[0118] The polarization curve of the membrane electrode was tested by passing 1 mol / L KOH as the electrolyte at 80°C. Figure 1 As shown, from Figure 1It can be seen that the membrane electrode prepared using platinum atom cluster catalyst has excellent activity and can achieve extremely high current density. 2A / cm at 80℃ 2 The stability of the membrane electrode was tested under constant current, such as Figure 2 As shown, from Figure 2 It can be seen that the membrane electrode provided by the present invention has excellent stability.

[0119] Example 2

[0120] The method of Example 1 is the same, except that the cathode uses 10 wt% Pt / C catalyst. The loading amount of the cathode catalyst is 1.0 mg / cm 2 The loading of the anode nickel-iron based catalyst is 2 mg / cm 2 .

[0121] The 10 wt% Pt / C catalyst was prepared according to Example 5 of 202210168801.3.

[0122] The membrane electrode was installed into the electrolytic cell for testing.

[0123] The polarization curve of the membrane electrode was tested by passing 1 mol / L potassium hydroxide solution as the electrolyte at 80°C. Figure 3 As shown, from Figure 3 It can be seen that when the amount of platinum is reduced to 0.1 mg / cm 2 It still has excellent activity and can achieve a very high current density. 1.5A / cm at 80℃ 2 The stability of the membrane electrode was tested under constant current, such as Figure 4 As shown, from Figure 4 It can be seen that the membrane electrode provided by the present invention has excellent stability.

[0124] Example 3

[0125] The method of Example 1 is the same, except that the cathode uses 20 wt% Pt / C catalyst. The cathode catalyst loading is 0.4 mg / cm 2 The loading of the anode nickel-iron based catalyst is 2 mg / cm 2 .

[0126] The 10 wt% Pt / C catalyst was prepared according to Example 3 of 202210168801.3.

[0127] The membrane electrode was installed into the electrolytic cell for testing.

[0128] The polarization curve of the membrane electrode was tested by passing 1 mol / L potassium hydroxide solution as the electrolyte at 80°C. Figure 5 As shown, from Figure 5It can be seen that when the amount of platinum is reduced to 0.08 mg / cm 2 It still has excellent activity and can achieve very high current density.

[0129] Comparative Example 1

[0130] The method of Example 1 is followed, except that the cathode uses a commercial Johnson Matthey 40 wt% Pt / C catalyst. The cathode catalyst loading is 1 mg / cm 2 The loading of the anode nickel-iron based catalyst is 2 mg / cm 2 .

[0131] The polarization curve of the membrane electrode was tested by passing 1 mol / L potassium hydroxide solution as the electrolyte at 80°C. Figure 6 As shown, from Figure 6 It can be seen that when the commercial Pt nanocrystalline catalyst is used to prepare the membrane electrode, when the platinum dosage is 0.4 mg / cm 2 At 80°C, the activity is still lower than that of the membrane electrode provided by the present invention. 2 The stability of the membrane electrode was tested under constant current, such as Figure 7 As shown, from Figure 7 It can be seen that the membrane electrode voltage prepared by commercial agents rises rapidly and has poor stability.

[0132] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A membrane electrode for producing hydrogen by water electrolysis, characterized in that: The membrane electrode comprises a diaphragm and a cathode diffusion layer. A cathode catalyst is coated on one side of the cathode diffusion layer adjacent to the diaphragm. The cathode catalyst comprises a supported platinum atom cluster catalyst modified with sulfur and / or nitrogen.

2. The membrane electrode according to claim 1, wherein: The platinum loading in the membrane electrode is not more than 0.4 mg / cm 2 , more preferably not more than 0.1 mg / cm 2 , more preferably 0.05-0.1 mg / cm 2 ; And / or, in the membrane electrode, the cathode catalyst content is not more than 1.5 mg / cm 2 , more preferably not more than 1 mg / cm 2 , more preferably 0.2-1 mg / cm 2 .

3. The membrane electrode according to claim 1 or 2, wherein: The sulfur and / or nitrogen modified supported platinum atom cluster catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0, and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8; Preferably, in the sulfur and / or nitrogen modified supported platinum atom cluster catalyst, the mass fraction of platinum is 1-70%.

4. The membrane electrode according to claim 3, wherein: The sulfur- and / or nitrogen-modified supported platinum atom cluster catalyst includes a nitrogen-modified platinum-carbon catalyst and / or a sulfur-modified platinum-carbon catalyst; Preferably, the nitrogen-modified platinum-carbon catalyst comprises nitrogen-modified conductive carbon black and platinum metal supported thereon, the nitrogen-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 1.0 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.8, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV; Preferably, the sulfur-modified platinum-carbon catalyst comprises sulfur-modified conductive carbon black and platinum metal supported thereon, and the sulfur-modified platinum-carbon catalyst has no Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.8 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.5, and the Pt 4f 7 / 2 characteristic peak in the XPS spectrum is located above 71.6 eV.

5. The membrane electrode according to claim 4, wherein: The conductive carbon black in the nitrogen-modified conductive carbon black and the sulfur-modified conductive carbon black is independently selected from one or more of EC-300J, EC-600JD, ECP600JD, VXC72, VXC72R, Black pearls 2000, PRINTEX XE2-B, PRINTEX L6 and HIBLAXK 40B2; Preferably, in the XPS analysis of the conductive carbon black, the oxygen content is greater than 4 mass %; Preferably, the resistivity of the conductive carbon black is less than 10Ω·m; Preferably, the specific surface area of ​​the conductive carbon black is 200-2000m 2 / g.

6. The membrane electrode according to claim 4 or 5, wherein: In the nitrogen-modified platinum-carbon catalyst, the mass fraction of platinum is 1-20%, preferably 5-15%, based on the total mass of the nitrogen-modified platinum-carbon catalyst; Preferably, when the platinum content of the nitrogen-modified platinum-carbon catalyst is less than 6% by mass, the ratio of the normalized peak intensity per unit mass of the Pt(111) characteristic peak to the half-maximum full width is not greater than 0.5 and the ratio of the normalized peak intensity per unit mass of the Pt(200) characteristic peak to the half-maximum full width is not greater than 0.4; Preferably, the nitrogen element in the nitrogen-modified conductive carbon black exists in the form of pyrrolic nitrogen; Preferably, the nitrogen content of the nitrogen-modified conductive carbon black is 0.1-10% by mass, preferably 0.2-5% by mass; Preferably, the nitrogen-modified platinum-carbon catalyst has a nitrogen content of 1s Except for the characteristic peak between 399-400.5eV, there is no other characteristic peak between 395-405eV.

7. The membrane electrode according to claim 4 or 5, wherein: The total sulfur content in the sulfur-modified conductive carbon black is greater than or equal to the surface sulfur content, preferably the total sulfur content is more than 1.2 times the surface sulfur content, more preferably more than 1.5 times; Preferably, the total sulfur content in the sulfur-modified conductive carbon black is 0.1-8% by mass, more preferably 0.5-6% by mass; Preferably, the surface sulfur content of the sulfur-modified conductive carbon black is 0.1-6% by mass, preferably 0.5-3% by mass; Preferably, based on the total mass of the sulfur-modified platinum-carbon catalyst, the mass fraction of platinum is 5-70%, preferably 7-40%; Preferably, when the platinum content of the sulfur-modified platinum-carbon catalyst is less than 10% by mass, the sulfur-modified platinum-carbon catalyst does not have a Pt characteristic peak in the XRD spectrum, or the ratio of the unit mass platinum normalized peak intensity of the Pt (111) characteristic peak to the half-maximum full width is not greater than 0.6 and the ratio of the unit mass platinum normalized peak intensity of the Pt (200) characteristic peak to the half-maximum full width is not greater than 0.4; Preferably, the sulfur-modified platinum-carbon catalyst has a Pt 4f 7 / 2 characteristic peak located above 71.7 eV in the XPS spectrum.

8. The membrane electrode according to any one of claims 1 to 7, wherein: The preparation method of the supported platinum atom cluster catalyst modified by sulfur and / or nitrogen comprises the following steps: (1) nitrogen-modifying and / or sulfur-modifying conductive carbon black to obtain nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black; (2) removing the solvent from the uniform mixed solution containing nitrogen-modified conductive carbon black and / or sulfur-modified conductive carbon black, a platinum source and a solvent to obtain a precursor material; (3) heat treating the precursor material obtained in step (2) at 80-200° C. for 1-4 h in a reducing atmosphere to obtain a platinum atom cluster catalyst; Wherein, in step (1), the nitrogen modification of the conductive carbon black comprises: after the conductive carbon black is contacted with a nitrogen source in an aqueous solution, the water is removed, and the obtained product is subjected to high temperature treatment under an inert atmosphere to obtain nitrogen-modified conductive carbon black; preferably, the conditions of the high temperature treatment include: a temperature of 1000-1500° C. and a constant temperature time of 0.5-10 h; Wherein, in step (1), sulfur-modifying the conductive carbon black comprises: impregnating the conductive carbon black with a solution containing sulfur at 10-80° C. for 1-5 hours, and drying the impregnated product to obtain sulfur-modified conductive carbon black.

9. The membrane electrode according to claim 8, wherein: The nitrogen source is ammonia water and / or urea, and the mass ratio of the conductive carbon black to the nitrogen source calculated by the mass of the nitrogen element is 30:1-1:

2.

10. The membrane electrode according to claim 8, wherein: The solvent in the sulfur-containing solution is one or more of CCl4, CS2, cyclohexane, and n-hexane; Preferably, the concentration of sulfur in the sulfur-containing solution is 0.0004-0.02 g / mL; Preferably, the amount of sulfur used is 0.005-0.06 g relative to 1 g of the conductive carbon black.

11. The membrane electrode according to any one of claims 8 to 10, wherein: In step (2), the platinum source is one or more of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate and platinum acetylacetonate; and / or, in step (2), the solvent is one or more of water, an alcohol solvent or a ketone solvent; And / or, relative to 1g of the nitrogen-modified conductive carbon black and / or the sulfur-modified conductive carbon black, the amount of the platinum source used is 0.01-2.4g in terms of platinum element.

12. The membrane electrode according to any one of claims 8 to 11, wherein: In step (3), the reducing atmosphere comprises hydrogen, preferably a mixed atmosphere of hydrogen and an inert gas, more preferably a mixed atmosphere of hydrogen and nitrogen; preferably, hydrogen accounts for 5-30 volume % of the total gas.

13. The membrane electrode according to any one of claims 1 to 12, wherein: The cathode diffusion layer is also coated with an ionomer on one side adjacent to the diaphragm, and preferably the mass ratio of the cathode catalyst to the ionomer is 70-92:8-30; Preferably, the coating method of the cathode catalyst and ionomer comprises: coating the slurry to be coated on one side of the cathode diffusion layer and drying; the slurry to be coated comprises a supported platinum atom cluster catalyst modified with sulfur and / or nitrogen, an ionomer solution and a solvent; Preferably, the mass dosage of the ionomer solution is 0.9-4.5 times that of the cathode catalyst; Preferably, the solvent comprises water and a dispersion solvent, and the dispersion solvent is preferably selected from C1-C4 alcohols.

14. The membrane electrode according to any one of claims 1 to 13, wherein: The cathode diffusion layer is selected from porous carbon materials, preferably at least one of carbon paper, carbon cloth and carbon felt; And / or, the membrane is selected from at least one of an anion exchange membrane, a PPS membrane and asbestos cloth.

15. The membrane electrode according to any one of claims 1 to 14, wherein: The membrane electrode further comprises an anode diffusion layer, and the diaphragm is disposed between the anode diffusion layer and the cathode diffusion layer; Preferably, the anode diffusion layer is coated with an anode catalyst on one side adjacent to the diaphragm, and the anode catalyst is preferably selected from at least one of iridium oxide, nickel oxide, iron oxide, cobalt oxide, nickel ferrite, nickel-iron double hydroxide, nickel sulfide, nickel-iron-cobalt oxide and nickel-iron-cobalt hydroxide; Preferably, the anode diffusion layer is selected from at least one of titanium foam, titanium felt, titanium mesh, nickel foam, nickel mesh and nickel felt.

16. Application of the membrane electrode according to any one of claims 1 to 15 in hydrogen production by water electrolysis under alkaline conditions, preferably in hydrogen production by water electrolysis by AEM, preferably in said application, the current density is not less than 0.8 A / cm 2 , and further preferably the current density is 0.8-6A / cm 2 .

Citation Information

Patent Citations

  • Platinum-carbon catalyst as well as preparation method and application thereof

    CN116646540A

  • Platinum-carbon catalyst as well as preparation method and application thereof

    CN116646544A

  • Platinum-carbon catalyst as well as preparation method and application thereof

    CN116676617A